Bonzai Unusual Effects: A Case Report - Halise Akça; Nilden Tuygun; Can Demir Karacan (Galenos Yayinevi, 2019)
The use of synthetic cannabinoids is a major health problem in all over the world as well as in our country. These products are synthetic substances created via mixture of cannabinoids and various plants. They are easy to access, inexpensive and undetectable on routine toxicological screening, leading to common use in the adolescent age group. In addition to physical effects, such as nausea, vomiting, sweating, tachycardia, hypertension, chest pain and altered consciousness, psychoactive effects, such as agitation, anxiety, altered perception, hallucinations and panic attacks, are also seen. Here, we present an adolescent patient with bradycardia and acute altered consciousness after bonzai use.